Corporate characteristics and environmental management accounting (EMA) implementation: evidence from Malaysian public listed companies (PLCs) - Mokhtar, Norsyahida; Jusoh, Ruzita; Zulkifli, Norhayah (Elsevier Inc. Ltd., 2016)
Adopting the contingency theory framework, this study investigated the extent to which Malaysian public listed companies (PLCs) implement environmental management accounting (EMA) and whether the implementation varies across corporate characteristics. Five corporate characteristics, namely, environmental sensitivity of industry, company size, ownership status, Environmental Management System (EMS) adoption and the proportion of non-executive directors (NEDs), were examined. The results,derived from postal questionnaires, indicate that the extent of EMA implementation was moderate and that more emphasis was placed on environmental cost effectiveness activities. The results also imply that complying with environmental regulations is more important than incorporating EMA information into performance measurement, control and reporting. Except for ownership status, the extent of EMA implementation, however, did not vary among corporate characteristics, and thus, provides limited support to contingency theory in explaining the extent of EMA implementation among Malaysian PLCs.